2016
DOI: 10.1177/2048872616652261
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the diagnostic utility of D-dimer measurement in patients with acute aortic syndrome

Abstract: This study demonstrated that the D-dimer test can distinguish acute aortic syndrome from other diseases presenting with acute chest pain with high sensitivity and modest specificity. Using the D-dimer approach presents limitations with some subtypes of acute aortic syndrome, such as intramural haematoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
33
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 19 publications
0
33
0
3
Order By: Relevance
“…Within 680 studies identified by the systematic database research, 12 studies were selected for full-text review ( Figure 1) and four studies met all the inclusion criteria. 16,[28][29][30] Three studies were designed to investigate the diagnostic test characteristics of ADD-RS plus DD < 500 ng/mL, [28][29][30] and one investigated the integration of ADD-RS with DD < DD age-adj . 16 The study characteristics are summarized in Table 2 and the final diagnoses of the participant patients are detailed in Table S3.…”
Section: Literature Searchmentioning
confidence: 99%
See 4 more Smart Citations
“…Within 680 studies identified by the systematic database research, 12 studies were selected for full-text review ( Figure 1) and four studies met all the inclusion criteria. 16,[28][29][30] Three studies were designed to investigate the diagnostic test characteristics of ADD-RS plus DD < 500 ng/mL, [28][29][30] and one investigated the integration of ADD-RS with DD < DD age-adj . 16 The study characteristics are summarized in Table 2 and the final diagnoses of the participant patients are detailed in Table S3.…”
Section: Literature Searchmentioning
confidence: 99%
“…16,[28][29][30] Three studies were designed to investigate the diagnostic test characteristics of ADD-RS plus DD < 500 ng/mL, [28][29][30] and one investigated the integration of ADD-RS with DD < DD age-adj . 16 The study characteristics are summarized in Table 2 and the final diagnoses of the participant patients are detailed in Table S3. The case mix of AASs was similar among studies, with acute aortic dissection representing the most frequent subtype and intramural aortic hematoma or penetrating aortic ulcer accounting for most of the other cases.…”
Section: Literature Searchmentioning
confidence: 99%
See 3 more Smart Citations